2020
DOI: 10.1097/brs.0000000000003236
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Preoperative Mental Health on PROMIS Physical Function Outcomes Following Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Study Design. Retrospective. Objective. To demonstrate whether preoperative mental health status can be predictive of postoperative functional outcomes as measured by Patient-Reported Outcome Measurement Information System Physical Function (PROMIS PF) following minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Summary of Background Data. There is a paucity of scientific investigations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…This study found that patients with preoperative psychological disorder had corresponding worse physical function preoperatively as indicated by lower PROMIS PF scores at the preoperative baseline. This is consistent with previous literature that preoperative psychological disorder is associated with a patient's physical disability before spinal surgery [21][22][23][24]. Joon et al [21] demonstrated that patients with worse preoperative mental health were demonstrated to have worse preoperative PROMIS PF scores following minimally invasive transforaminal lumbar interbody fusion, what's more, patients with low mental health continue to report signi cantly worse physical function throughout the postoperative convalescence period.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that patients with preoperative psychological disorder had corresponding worse physical function preoperatively as indicated by lower PROMIS PF scores at the preoperative baseline. This is consistent with previous literature that preoperative psychological disorder is associated with a patient's physical disability before spinal surgery [21][22][23][24]. Joon et al [21] demonstrated that patients with worse preoperative mental health were demonstrated to have worse preoperative PROMIS PF scores following minimally invasive transforaminal lumbar interbody fusion, what's more, patients with low mental health continue to report signi cantly worse physical function throughout the postoperative convalescence period.…”
Section: Discussionsupporting
confidence: 90%
“…The impact of pre-operative mental health on subsequent patient reported outcomes remain controversial in the literature. While Yoo et al showed that patients with worse pre-operative mental health scores had worse postoperative outcomes, 14 other studies have shown poor correlation of baseline mental health with post-surgical patient reported outcome measures. 15 - 17 …”
Section: Discussionmentioning
confidence: 96%
“…For MIS TLIF specifically, patients demonstrating worse preoperative mental health status had worse postoperative PROMIS-PF. All patients demonstrated similar levels of improvement from baseline for shorter timepoints; however, those with worse mental health status demonstrated worse postoperative improvement 1 year after MIS TLIF [ 14 ]. This trend was similarly found among patients with isthmic spondylolisthesis, as the mean pain and disability PROMs were lower and long-term improvements across PROMs were less frequent among patients presenting with poorer preoperative SF-12 MCS [ 15 ].…”
Section: Discussionmentioning
confidence: 99%